Early Calculation of Forces and Means to Reduce the Risk of Emergencies (Fires) - Ruziev Suxrob Toirovich; Yasakov Zikrilla Xayrullaevich; Achilov Anvar Mamarasulovich (Research Parks Publishing LLC, 2023)
The article conducts research on preventing and eliminating the consequences of an emergency (fire), in particular, substantiating problems that are becoming one of the most pressing issues in the field of fire safety through solutions based on research results.